Human Awareness Support by Changing Values of Hidden Factors of Input Stimuli Dynamically - TAKAGI, Hideyuki; IKEDA, Keisuke; LAI, WeiQiang (2018 9th International Conference on Awareness Science and Technology (iCAST), 2018)
We propose an awareness support system that helps a user to be aware of the reason of his/her evaluations. Based on our proposed definition of human awareness mechanism, we extract hidden factors of input information using an autoencoder neural networks and implement its decoder part into an awareness support system. The big feature of this system is to let a user change the values of the extracted hidden factors manually and observe the system outputs that change according to the changes of hidden factors. Experimental results using a task of generating facial emotions with 21 human subjects have shown the effectiveness of this approach.